The children are alright: Revisiting the impact of parental migration in the Philippines - Marjorie Pajaron; Cara T. Latinazo; Enrico G. Trinidad (Global Labor Organization (GLO), 2020)
The Philippine government has focused most of its migration policy initiatives to encouraging international labour migration and protecting the rights of Filipino migrant workers. However, government interventions and aids to left-behind families and children left much to be desired. This paper aims to provide a better understanding of the impact of parental migration on the welfare of left-behind children in the Philippines so that policies can be devised to support them. This study's analytical methods (instrumental variable analysis and propensity score matching) enable it to address several issues in migration research including endogeneity, migrant selectivity and community (regional) context, using previously unexamined nationally representative data from the Philippines. Our results suggest an overall positive impact on education, work, and temper of left-behind children. However, they tend to be more physically sickly. This warrants government attention to preclude any long-term negative health effects.
Keywords: 330; Parental Migration; Children's Welfare; Instrumental Variable; PSM